Design of an ultra-low-voltage low-power current reference - He, Xinyu (Nanyang Technological University, 2023)
This dissertation presents a low voltage CMOS current reference operating in the subthreshold region. Implemented using TSMC-40 nm process technology, it consumes 0.48 μW at a supply voltage of 0.4 V, with an average output current of 298.2nA. The design incorporates frequency compensation and temperature compensation to achieve lower temperature coefficient. By employing piecewise compensation, this circuit achieves a temperature coefficient of 18.19 ppm/℃ in the TT corner. Furthermore, in the Monte-Carlo simulation, the mean T.C. is 33.8 ppm/℃, and the process sensitivity is 7.2% under 100 samples. The circuit operates within a temperature range of -20℃ to 80℃.This has demonstrated robust temperature insensitivity. The Figure-of-Merit for total output current variation is 0.25%, surpassing other MOSFET current reference circuits. With its low supply voltage and low T.C., the proposed work is suitable for portable and implantable medical applications with strict requirements.